Flexible X-ray imaging detectors using scintillating fibers. (1st October 2022) - Wilbur, S.; Anastopoulos, C.; Angelmahr, M.; Asfis, G.; Koch, J.; Lindblom, M.; Lohwasser, K.; Margulis, W.; ,
Abstract: We present early design and simulation work on a novel X-ray imaging detector. The intent of the FleX-RAY project is to create a digital X-ray detector that is capable of producing high-resolution images, is flexible enough to produce an image on a curved surface, and is capable of self-reporting its final shape. The X-rays will be detected on a sheet of scintillating optical fibers, which will guide the scintillation light to single-photon avalanche photodiodes. This setup allows the electronics and hardware to be moved out of the path of the X-ray beam, limiting the need for additional shielding. Self-shape-reporting will be achieved using a flexible ultra-thin glass substrate with optical waveguides and Bragg gratings, processed by femtosecond laser point-by-point writing. The functionalized glass substrate allows precise measurement of strains, which can be used to calculate the shape.